Carbon capture and storage in China's power sector: Optimal planning under the 2 °C constraint. (1st April 2020) - Wang, Peng-Tao; Wei, Yi-Ming; Yang, Bo; Li, Jia-Quan; Kang, Jia-Ning; Liu, Lan-Cui; Yu, Bi-Ying; Hou, Yun-Bing; Zhang, Xian
Highlights: A source–sink optimization model is proposed for the optimal CCS planning. 175 GW coal-fired power plants need to be retrofitted with CCS under the 2 °C constraint. Four large-scale power plant clusters as candidates for CO2 hubs and clusters have been identified. A CO2 storage site can be found within an average radius of 115 km from these power plants. The minimum abatement cost is USD 1212 billion for the national-level CCS layout. Abstract: Carbon capture and storage (CCS) has been widely recognized as a key technology to reduce CO2 emissions in the power sector. China's power sector needs to achieve large-scale emission reductions through CCS technologies to contribute to limiting the global temperature rise to less than 2℃. The best source–sink matching directly affects total mitigation costs for the power sector. However, China has not yet established an optimal CCS plan. This study evaluates the least-cost source–sink relationship and cluster development opportunities for CCS in China under the 2 °C constraint. The results show that 165 existing coal-fired power plants, which have an installed capacity of approximately 175 GW, need CCS retrofitting and can find a suitable CO2 storage site within an average radius of 115 km. The total captured CO2 is 17.42 billion tons in Northeast, North, East, Northwest, and South regions with the share of 10.79% (1.88 GtCO2 ), 31.29% (5.45 GtCO2 ), 35.25% (6.14GtCO2 ), 22.39% (3.90GtCO2 ), and 0.27% (47MtCO2 ), respectively. Approximately 90% of captured CO2 can be stored in the Songliao, Bohai Bay, and Subei basins. In addition, 23% of the emission reductions can be achieved through CO2 -enhanced oil recovery. The total mitigation cost is USD 1212 billion and the revenue generated from CO2 -enhanced oil recovery is USD 377 billion. Overall, it provides the least-cost source–sink layout and cluster development opportunities for CCS development under the 2 ℃ constraint, which can serve as a basis for large-scale CCS adoption in China.